Relationship between Knowledge of Occupational Health and Safety (OHS) and the Occupational Accidents at the Kotamobagu Regional General Hospital - Ellen Pesak; Jane Annita Kolompoy; Sulianty T Mamonto; Bongakaraeng Bongakaraeng; Jusuf Kristianto (Jurnal Health Sains, 2023)
This research on knowledge about Occupational Health and Safety (OHS) aims to determine the relationship between knowledge about Occupational Health and Safety with work accidents at Kotamobagu Regional Hospital. The type of research is quantitative analytic with cross sectional design. The study population was all employees at Kotamobagu Regional Hospital, totaling 677 people. The research sample was determined by cluster random sampling, where the research sample was taken from each section proportionally and then determined randomly, so that 150 respondents were selected. Data analysis used in this research includes univariate analysis and bivariate analysis using Chi-Square test to determine the relationship between variables. The results showed that there were 145 people (97%) respondents had good knowledge about OHS, as many as 72 people (48%). who experienced work accidents. The results of the relationship test between variables showed a value of (p = 0.413) which indicates that there is no significant relationship between knowledge about Occupational Health and Safetyand work accidents at Kotamobagu Hospital.